Implementation of Quality Function Deployment (QFD) for Decision Making in Improving Integrated Academic Information System - Mardhiana, Hawwin; Rachmawati, Dina; Winati, Familia Dwi; Yamani, Achmad Zaki (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2022)
Academic Information System is a tool to support academic activities in implementing education in institutions effectively and efficiently. Institut Teknologi Telkom Surabaya is an institution that already has an integrated academic information system called I-Gracias. I-Gracias uses a single-user system for all applications. Most users of I-Gracias are students, so student satisfaction with integrated academic information system services can be used as benchmarks in determining I-Gracias improvement plans. One method used for the I-Gracias improvement process is the Quality Function Deployment (QFD) method. This method determines the student's desire for I-Gracias using the House of Quality (HOQ) matrix. The result of this research is that the QFD method can prioritize technical responses to the main obstacles for students in using I-Gracias by correlating Voice of Consumer (VOC) and technical response. The highest priority for technical response is coordinating with other units with a technical importance rating of 620.9 and a relative weight value of 21%. Next is to update the module regularly, socialize i-Gracias, meet management targets, receive criticism and suggestions, carry out regular checks and recruit HR if needed as a sequence of improvements to i-Gracias.